A Multi-Agent organizational modeling at the backend of a metaversity - Nóbrega, Germana; Serrano, Milene; Serrano, Maurício; Cruz, Fernando; Freitas, Fred (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2025)
Advances on Artificial Intelligence (AI) have inspired the design of innovative applications for education. However, its poorly planned use has led to a number of pitfalls mapped in literature, along with recommendations towards responsible AI. We are currently investigating how Multi-Agent Systems (MAS) can enhance higher education. In this paper, we introduce a MAS organizational modeling of typical campus, at the backend of a decentralized metaverse platform. The model is proposed to be scalable and refinable, such as to fit specific requirements of institutions eventually reusing it, and serve as a sand-box for teaching/research AI for education (and education for AI). Model dissemination and instantiation should provide empirical evidence for further analysis.